Micro-needling: current state of knowledge and clinical applications: a review - Ciozda, Agnieszka; Firlej, Ewelina; Kowalska, Wioleta; Kwiatkowska, Magdalena; Bartosińska, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Micro-needling mesotherapy is one of the increasingly popular treatments in dermatology clinics due to its wide range of effects on the skin. During the procedure, “micro-channels” are created in the epidermis, which remain open for a short period, allowing for the deeper delivery of selected active substances tailored to the skin’s needs. In addition, micro-needling induces micro-injuries that stimulate the skin’s repair processes, which are essential for tissue regeneration. The aim of the review is to create a practical guide for applying this method in clinical practice. An extensive review of the literature from the past 10 years was conducted using the PubMed database. The database was searched using the following keywords: “micro-needling”, “micro-needle”, “percutaneous collagen induction”, and “dermaroller”. The article is based on previously conducted studies and does not include any new research involving humans or animals.